Village Officials’ Perceptions of the Potential for Fraud in Village Fund Management with Moral Reasoning as a Moderating Variable - Nanak Andrean Prayoga; Saring Suhendro; Liza Alvia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of collusion, ego, and fraud hexagon elements on the potential for fraud in village fund management, as well as the role of moral reasoning as a moderating variable. The results indicate that collusion and ego have a positive and significant effect on the potential for fraud, meaning that higher levels of collusion and ego among village officials increase the likelihood of fraud. Conversely, factors such as pressure, capability, opportunity, and rationalization do not have a significant impact on fraud potential. Further findings reveal that moral reasoning significantly weakens the influence of pressure, collusion, opportunity, rationalization, and ego on fraud potential. However, the capability element remains significant and cannot be moderated by moral reasoning. These results underscore the importance of strengthening moral reasoning through ethics and integrity training for village officials to reduce the potential for fraud in village fund management.